Resistor tester machine using Lightbus automation system - Sommar Achin (Universiti Malaysia Perlis, 2008)
Lightbus in automation is a new bus technology that has been introduce in industry system by one of the bus automation company well known as Beckhoff Automation. Dispite of it efficiency and advantages characteristic at the lightbus system, there are no denied that this system shall be replace the old bus system. In this project Lightbus system prototype have been use to generate the skill and training in designing an automation system using lightbus sytem. This project consist three main part such as hardware, software and program. On the hardware session is devide into two sub division such as hardware for lightbus system and hardware for the Resistor Tester Machine. Although this project is more focus on software and project session that the method to make hardware configuration and programming process. The value of resistor range are check between 18.7kΩand 29.3kΩ. If the value below the 18.7kΩ or above than 29.3kΩ the resistor is reject. Overall Resistor Tester Machine Using Lightbus Automation System in this project succeed.